Bodies of Knowledge : Embodied Rhetorics in Theory and Practice - Moeller, Marie E.; Knoblauch, A. Abby (Book collections on Project MUSE., 2022)
"Challenges the homogenizing (mis)understandings of knowledge construction and provides a complex discussion of what happens when we do not attend to embodied rhetorical theories. Language is always a reflection of culture, to attempt to erase language and knowledge that reflect minoritized and historically excluded cultural experiences obscures the legitimacy of such experiences both within and outside the academy"--